Quantitative Analysis of Science and Chemistry Textbooks for Indicators of Reform: A complementary perspective - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2010)
In this study, multiple thematically based and quantitative analysis procedures were utilized to explore the effectiveness of Turkish chemistry and science textbooks in terms of their reflection of reform. The themes gender equity, questioning level, science vocabulary load, and readability level provided the conceptual framework for the analyses. An unobtrusive research method, content analysis, was used by coding the manifest content and counting the frequency of words, photographs, drawings, and questions by cognitive level. The context was an undergraduate chemistry teacher preparation program at a large public university in a metropolitan area in northwestern Turkey. Forty preservice chemistry teachers were guided to analyze 10 middle school science and 10 high school chemistry textbooks. Overall, the textbooks included unfair gender representations, a considerably higher number of input and processing than output level questions, and high load of science terminology. The textbooks failed to provide sufficient empirical evidence to be considered as gender equitable and inquiry-based. The quantitative approach employed for evaluation contrasts with a more interpretive approach, and has the potential in depicting textbook profiles in a more reliable way, complementing the commonly employed qualitative procedures. Implications suggest that further work in this line is needed on calibrating the analysis procedures with science textbooks used in different international settings. The procedures could be modified and improved to meet specific evaluation needs. In the Turkish context, next step research may concern the analysis of science textbooks being rewritten progression.
Keywords: Textbook evaluation; Educational reform; Curriculum reform; Inquiry-based teaching; Teacher education; Gender equity; Questioning level; Science vocabulary; INQUIRY; EDUCATION